1989
DOI: 10.1002/jrs.1250200103
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of the NaH2PO4 crystal

Abstract: Room-temperature and low-temperature (10 K) Raman spectra of a single crystal NaH,PO, were obtained for various polarizations. The polarization characteristics of the Raman spectra remained unchanged throughout the whole temperature range studied. This confirms that there is no phase transition in this crystal at least down to 10 K. High-frequency H modes showed the well known ABC-type three-band structure and correlated with 0-H --* 0 bond lengtb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…These spectral characteristics were previously observed in a variety of strong hydrogen bonded solids having O … O distances varying from 2.45 to 2.70 Å, including Ca Ba (HPO 4 ) 2 [23], N(CH 3 ) 4 H 2 PO 4 $ H 2 O [24], and NaH 2 PO 4 [25]. In the present case, these bands (see Figs.…”
Section: Oeh Group Vibrationssupporting
confidence: 53%
“…These spectral characteristics were previously observed in a variety of strong hydrogen bonded solids having O … O distances varying from 2.45 to 2.70 Å, including Ca Ba (HPO 4 ) 2 [23], N(CH 3 ) 4 H 2 PO 4 $ H 2 O [24], and NaH 2 PO 4 [25]. In the present case, these bands (see Figs.…”
Section: Oeh Group Vibrationssupporting
confidence: 53%
“…These bands are attributed to the stretching vibrations of the monohydrogen phosphate units. Choi et al [29] published spectra of NaH 2 PO 4 ; however these authors did not tabulate or mark the position of the peaks. Therefore, it is very difficult to make any comparison of the peak positions of goyazite and that of published data by Choi et al Casciani and Condrate [30] reported bands assigned to these vibrational modes for Ca(H 2 PO 4 ) 2 at 876 and 901 cm À1 .…”
Section: Vibrational Spectroscopymentioning
confidence: 98%
“…The 2800}1700 cm\ range corresponds to the OH modes of HPO\ groups characterized by three broad bands of ABC type. Similar bands have been observed in strong hydrogen bonded crystals, such as CaBa(HPO ) (13) and PbHPO (14). The presence of bands in the region 1400}1200 cm\ is characteristic of hydrogen monophosphate groups (12).…”
Section: A Initial Characterizationmentioning
confidence: 55%